Training Penjernihan Air Sumur Gali Masyarakat di Kampung Warbo Arso 7, Distrik Arso Barat, Keerom - Lantang , Daniel; Menufandu, Herlina; Rampa, Ester; Sinaga, Herlando; Daawia, Daawia (Bakti Hayati: Jurnal Pengabdian Indonesia, 2024)
Water is the main composition in the body, the amount of water content contained in the body is about 50-80%, depending on age, most of the human body consists of fluids, so the body really needs adequate fluid intake. This fluid intake is obtained from drinking water and food. Based on a survey conducted, the physical appearance of community dug well water in Warbo village Arso 7, West Arso district, is generally cloudy, smelly in colour and quite high in lime. This service aims to provide training to the Warbo village community so that they can use a dug well water purification tool and can use clean water. The method used in this service is the direct partner participation method, which explains the sequence of how the filter is connected to the daft machine or pump. The results of the service activities carried out on May 2024 were attended by 12 people. After a week of installing the filter, the people who became the sample or who were selected to receive filter assistance felt happy because the well water they used was no longer coloured, smelled, and cloudy.